Case report: post COVID-19 encephalopathy and oral cenesthopathy - Ju-I Wu; Shwu-Hua Lee; Pei-Jung Chen (BMC Psychiatry)
Abstract Post-COVID-19 encephalopathy is a neurological complication characterized by cognitive impairment, memory loss, and other neuropsychiatric symptoms in COVID-19 survivors. Oral cenesthopathy, a rare somatic delusion characterized by unusual oral sensations without physical findings, is typically associated with affective disorders and schizophrenia. This case report describes a 73-year-old female who developed post-COVID-19 encephalopathy, presenting initially with cognitive decline, followed by major depression and oral cenesthopathy 16 months after the infection. Comprehensive investigations excluded autoimmune encephalitis, Creutzfeldt-Jakob disease, and other structural or vascular abnormalities. Treatment with Aripiprazole and Carbamazepine resulted in partial improvement, though symptom control was limited by medication side effects. This case represents a rare presentation of long COVID syndrome, highlighting the complex neuropsychiatric sequelae of COVID-19. Further research is needed to explore the pathophysiology, treatment strategies, and long-term impacts of such manifestations.